(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2024)
The contribution presents some of the methods and operational choices undertaken in the realisation of the new catalogue of Foscolo’s letters starting from the analysis of the collections of Giuseppe Martini, Natale Mazzol. and Maria Calzavara and Federico Gentili di Giuseppe. The reconstruction of the collections and the events that affected them, the current location of the autographs and their analysis will provide an example of the methodological approach followed and the effort to update the entire corpus.